If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -1z = 12 + -1z Add 'z' to each side of the equation. -7 + -1z + z = 12 + -1z + z Combine like terms: -1z + z = 0 -7 + 0 = 12 + -1z + z -7 = 12 + -1z + z Combine like terms: -1z + z = 0 -7 = 12 + 0 -7 = 12 Solving -7 = 12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| a=1+8*2+(8-4)*7 | | 4x(3x)+5-7=56 | | -3x+7=5-4x | | -6x-13=-61 | | 9=5+9b | | 6l+3l=5.4 | | sin(5x)=3sin(3x) | | 8-9x=21x-7 | | y=f(-x) | | 2x-13=12-3x | | 6a-2b=32 | | -8-9x=21-7 | | y=f(x)-8 | | -1.8=-.6 | | 9(t-8)/4 | | (4y-9)(5-y)=0 | | -3-x=4-2x | | 10=a(20+23)(20-17) | | 280=x(2x+6) | | (1/x-1/6x)^-1 | | -6=-7p+2+8p | | 5(r+a)-5= | | y=f(x-8) | | 9(y+4)=5(y-4) | | (((4x)^-5)(6x)^-2)/((3x)^-3 | | a+4.9=7.6 | | -20+2x=5-3x | | 6x(-7/2) | | -20+2x=3+5 | | u/9 = 8 | | y=f(x+8) | | 6(13-5s)=62 |